Design of Smart Door Lock System Using Face Recognition and Mask Detection Based on Viola-Jones Algorithm with Android Integration - Tania Nurindini; Mitodius Nicho Swacaesar; Rathalia Widita Astika; Hendrik Purwanto; Rieke Adriati Wijayanti; Mochammad Taufik (Jurnal Jaringan Telekomunikasi, 2023)
Indonesia has been affected by COVID-19 since 2020. In order to stop the virus spreading, the government puts Large Scale Social Restrictions. There is no denying that during this pandemic, criminality is increasing, and this is due to nothing other than the need to survive. The stealing and invading of homes is one of the crimes that have increased. Additionally, the government has strengthened health procedures to require that individuals wear masks while doing activities outside. A system that can identify faces and identify the use of masks was developed in order to solve this issue. Face recognition is used to increase security, and mask detection systems work to enforce the wearing of masks when engaging in outside activities. Both of these technologies can be combined into a single smart door lock system for the home. The system will apply facial recognition identification when someone wants to enter the house and mask detection when they want to do activities outside the house. As a monitoring tool, data will be delivered in the form of an image via the user's Android. This is proven by the accuracy rates of facial identification of 95% and mask detection of 97.5% in this research.